Chemical self-healing system with novel microcapsules for corrosion inhibition of rebar in concrete. (January 2018) - Dong, Biqin; Ding, Weijian; Qin, Shaofeng; Han, Ningxu; Fang, Guohao; Liu, Yuqing; Xing, Feng; Hong, Shuxian
Abstract: Two kinds of chemically-triggered self-healing systems with novel microcapsules are designed to protect rebar from corrosion in concrete. X-ray micro-computed tomography (XCT) method is employed to non-destructively visualize the protection performance and quantitatively evaluate the efficacy of the self-healing system in a wet-dry cyclic accelerating corrosion test. Environmental scanning electron microscopy (ESEM) system equipped with texture element analysis microscopy (TEAM) is used to verify the results of XCT imaging analysis. The results reveal that the self-healing system-high efficiency is achieved by delaying the depassivation of the rebar and reducing the corrosion rate.